Rate-dependent ratcheting characteristics of high density polyethylene subjected to cyclic pulsating compression. (May 2023) - Ding, Peishan; Zheng, Xiaotao; Ma, Linwei
Abstract: Monotonic and pulsating cyclic compression tests were performed systematically based on high density polyethylene (HDPE). The compressive creep behaviors were further implemented to compare with the ratcheting deformation under the same peak stress level. Monotonic compression experiments reveal that HDPE shows obvious four-stage characteristics which are sensitive to temperature, but independent of the stress rate when the temperature is greater than 80 °C. Interestingly, the strain range during the stage III always starts at 7.4% and ends at 62.6% under various temperatures and stress rates. Moreover, the compressive ratcheting behavior of HDPE significantly depends on temperature T, peak stress σ p, stress rate σ ˙, stress amplitude Δ σ and stress ratio R, especially when T  ≥ 80 °C, σ p ≥15 MPa, σ ˙ ≤0.1 MPa/s and R  ≥ 0.8. Additionally, decreasing the stress rate or increasing the temperature will decrease the compressive modulus of HDPE. An approximate linear relationship between the creep strain rate and the ratcheting strain rate under different temperatures and stress ratios was observed. The compressive deformation characteristics of HDPE were compared with that of some other gasket materials, a universal phenomenon is found that the compressive ratcheting evolution with time can be characterized by creep approximately under the same loading peak stress, stress rate and temperature for various gasket materials when the stress ratio is greater than zero, which indicates that the ratcheting deformation for gaskets under cyclic loads may be estimated by the corresponding static creep strain in practical engineering.